Effectiveness of late and very late antivenom administration on recovery from snakebite-induced coagulopathy in French Guiana: a population-based studyResearch in context - Jean Marc Pujo; Stephanie Houcke; Guy Roger Lontsi Ngoulla; Vivian Laurent; Boubacar Signaté; Rémi Mutricy; Alexis Frémery; Flaubert Nkontcho; Ibtissem Ben Amara; José María Gutiérrez; Dabor Resiere; Hatem Kallel (The Lancet Regional Health. Americas)
Summary: Background: Snakebite (SB) envenoming is an acute emergency requiring early care delivery. However, sometimes, patients can take several hours before receiving antivenom (AV). We conducted this study to assess the effectiveness of antivenom in the recovery of clotting parameters in patients consulting tardily after SB envenoming in French Guiana. The primary endpoint of our study was to investigate the time needed from SB to recovery from SB-induced coagulopathy. The secondary endpoint was to investigate the time needed from AV administration to recovery from SB-induced coagulopathy in patients receiving AV (late or very late administration). Methods: This prospective observational study was conducted in the Intensive Care Unit (ICU) of Cayenne General Hospital between January 2016 and September 2023. We included all patients hospitalized for SB envenoming who either did not receive AV or received it more than 6 h after SB. We excluded patients who received antivenom in less than 6 h from the SB and those who received incomplete AV doses. Findings: We included 58 patients in the No AV group, 51 in the late AV group (6 h ≤ AV < 12 h), and 50 in the very late AV group (AV≥12 h). The median age of patients was 42 years (IQR: 29–53), 65.4% were male and 34.6% were female (104 and 55 out of 159 patients) without difference regarding the demographic parameters between groups. Data regarding ethnicity was not available. The median time from SB to AV was 8.5 h (IQR: 6.9–10) in the late AV group and 21.1 h (IQR: 16.7–27.4) in the very late AV group (p < 0.001). The time from SB to normal clotting parameters was shorter in patients receiving late AV than in those receiving very late AV and those not receiving AV. No differences were observed in the time from SB and recovery of fibrinogen and activated partial thromboplastin time (aPTT) between very late AV and no AV. However, the International Normalized Ratio (INR) recovery was shorter in the very late AV group than in the no AV group. On the other hand, the time from AV to normal fibrinogen was shorter in patients receiving very late AV than in patients receiving late AV (Log-Rank = 0.020). Meanwhile, the time from AV to normal INR or normal aPTT was similar in patients receiving very late AV compared to patients receiving late AV (Log-Rank = 0.722 and 0.740, respectively). Interpretation: Late AV administration effectively reverses coagulopathic manifestations after SB envenoming. However, very late AV administration did not improve the correction of some clotting parameters when compared to patients not receiving AV. Our findings could be explained by the combination of venom toxicokinetics and the kinetics of the synthesis of clotting factors. Funding: No funding.